Effects of Volatile Anesthetics on Postoperative Ischemic Stroke Incidence - Dana Raub; Katharina Platzbecker; Stephanie D. Grabitz; Xinling Xu; Karuna Wongtangman; Stephanie B. Pham; Kadhiresan R. Murugappan; Khalid A. Hanafy; Ala Nozari; Timothy T. Houle; Samir M. Kendale; Matthias Eikermann (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Preclinical studies suggest that volatile anesthetics decrease infarct volume and improve the outcome of ischemic stroke. This study aims to determine their effect during noncardiac surgery on postoperative ischemic stroke incidence. Methods and Results This was a retrospective cohort study of surgical patients undergoing general anesthesia at 2 tertiary care centers in Boston, MA, between October 2005 and September 2017. Exclusion criteria comprised brain death, age <18 years, cardiac surgery, and missing covariate data. The exposure was defined as median age‐adjusted minimum alveolar concentration of all intraoperative measurements of desflurane, sevoflurane, and isoflurane. The primary outcome was postoperative ischemic stroke within 30 days. Among 314 932 patients, 1957 (0.6%) experienced the primary outcome. Higher doses of volatile anesthetics had a protective effect on postoperative ischemic stroke incidence (adjusted odds ratio per 1 minimum alveolar concentration increase 0.49, 95% CI, 0.40–0.59, P<0.001). In Cox proportional hazards regression, the effect was observed for 17 postoperative days (postoperative day 1: hazard ratio (HR), 0.56; 95% CI, 0.48–0.65; versus day 17: HR, 0.85; 95% CI, 0.74–0.99). Volatile anesthetics were also associated with lower stroke severity: Every 1‐unit increase in minimum alveolar concentration was associated with a 0.006‐unit decrease in the National Institutes of Health Stroke Scale (95% CI, −0.01 to −0.002, P=0.002). The effects were robust throughout various sensitivity analyses including adjustment for anesthesia providers as random effect. Conclusions Among patients undergoing noncardiac surgery, volatile anesthetics showed a dose‐dependent protective effect on the incidence and severity of early postoperative ischemic stroke.